Strategic tax collection and fiscal decentralisation: the case of Russia - Libman, Alexander; Feld, Lars P. (CESifo working papers, 2007)
In a centralized federation, where tax rates and taxation rules are set by the federal government, manipulating the thoroughness of tax auditing and the effectiveness of tax collection could be attractive for regional authorities because of a variety of reasons. These range from tax competition to principal-agent problems, state capture and benefits of fiscal equalisation. In this paper we discuss strategic tax auditing and collection from the perspective of fiscal federalism and test for strategic tax collection empirically using data of the Russian Federation. Russia's regional authorities in the 1990s have always been suspect of tax auditing manipulations in their favour. However, in the 2000s increasing bargaining power of the centre seems to induce tax collection bodies in the regions to manipulate tax auditing in favour of the federation. We find partial evidence in favour of both of these hypotheses.